2013
DOI: 10.20452/pamw.1964
|View full text |Cite
|
Sign up to set email alerts
|

Management and treatment goals in Polish patients with type 2 diabetes of short duration: results of the ARETAEUS2‑Grupa study

Abstract: and treatment goals in Polish patients with type 2 diabetes... 573 INTROduCTION Type 2 diabetes is a leading cause of cardiovascular disease, including coronary heart disease (CHD) and stroke, as well as of adult blindness, kidney failure, and nontraumatic lower limb amputations. 1,2 The UKPDS Study demonstrated that early intensive diabetes treatment is beneficial and reduces long-term risk of cardiovascular events and mortality. 3-5 It is estimated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 0 publications
2
18
2
Order By: Relevance
“…The patient and physician characteristics and the results related to diabetes control was described elsewhere [10]. Sixty per cent of all patients had HbA1c level above 7.0%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient and physician characteristics and the results related to diabetes control was described elsewhere [10]. Sixty per cent of all patients had HbA1c level above 7.0%.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed description of the ARETAEUS2--Grupa study design, protocol, questionnaire, inclusion criteria for the study, recruitment procedures of physicians and their patients and sample size calculations was published previously [8]. Briefly, ARETAEUS2-Grupa was a cross-sectional questionnaire-based study conducted in Poland (April-June 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Physicians and patients were recruited to those two arms separately. This paper on patients with T2DM lasting > 10 years concerns only patients participating in ARATAEUS2-Grupa Study; the results for patients with T2DM of short duration have been reported elsewhere [9].…”
Section: Methodsmentioning
confidence: 99%
“…Patient inclusion criteria for the study ARETAEUS2-Grupa Study included two groups of patients of any age and both genders: -those diagnosed with type 2 diabetes within the previous two years (after 1 April, 2010) [9] who met the same inclusion criteria as in the ARETAEUS1 Study [2]; -those diagnosed with type 2 diabetes more than ten years before the study commencement (before 2002), in order to obtain data on treatment and disease control in intermediate to long-lasting diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation